Pelatihan Digital Marketing untuk Meningkatkan Kemampuan Siswa SMK Negeri 1 Cikokol Tangerang - Rinintha Parameswari; Sutrisna Sutrisna; Alexander Alexander; Toni Yoyo (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Digital marketing training is an essential need in education, especially in vocational schools. This Community Service Program (PkM) aims to enhance the digital marketing skills of students at SMK Negeri 1 Cikokol Tangerang, preparing them for the workforce and entrepreneurship in the digital era.The training combines theoretical and practical approaches, covering digital marketing strategies, creative content creation, and social media management. The results show a significant improvement in students' understanding of digital marketing, creativity in content creation, and the ability to utilize platforms such as Instagram and TikTok for business.This program not only enhances students' competencies but also contributes to the integration of digital marketing into the school curriculum. Furthermore, it fosters industry collaboration and supports students in starting their own businesses.